Impact of SGRY on Beneficiaries and Non-Beneficiaries in Dimapur District of Nagaland - WALLING, I.; SHARMA, A. (Indian Journal of Hill Farming, 2015)
The study was conducted in Medziphema and Chumukedima blocks under the Dimapur District of Nagaland. A sample of 30 beneficiaries and 30 non- beneficiaries were selected from 7 villages based on proportionate random sampling procedure. The study reveals that average sample beneficiary’s respondent family has a literacy of 86.60 per cent and 86.28 per cent for non-beneficiary family. Agriculture was found to have the highest impact on occupation for both beneficiaries and non-beneficiaries (56.45 per cent and 55.43 per cent respectively). The highest land use was for crop production (53.25 per cent and 49.4 per cent respectively). The beneficiary families had a total income of Rs. 97156.66/- per annum compared to Rs. 81903.33/- per annum for non- beneficiaries. The total output of cropping per annum was Rs. 19016.66/- for beneficiaries and Rs. 16920/- for non- beneficiaries. The amount of savings was Rs. 11483.33/- and Rs. 7255/- for beneficiaries and non-beneficiaries, respectively. The activities undertaken in the selected villages under the scheme have all been successfully completed.